Pemikiran Ustadz Abdul Somad tentang Islam Moderat di Nusantara: Relevansi dalam Konteks Sosial dan Politik Kontemporer - Dika Putra Madya; Yauma Wulida Farhana; Dimas Surya Bekti; Valerina Rusmana Putri; Abdul Fadhil (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to examine Ustadz Abdul Somad's thoughts on moderate Islam and its relevance in the contemporary social and political context in Indonesia. Ustadz Abdul Somad is known for his approach that prioritizes the values of tolerance, diversity, and moderation in religion. This study uses a qualitative approach with data collection techniques through library research on books, journal articles and other reading sources. Data analysis was carried out using the content analysis method to identify and interpret the main ideas related to moderate Islam. The results of the study show that Ustadz Abdul Somad's thinking has made a significant contribution to strengthening religious moderation in Indonesia, especially in facing the growing social and political challenges. His thoughts are relevant to the dynamics of Indonesia's diversity, as well as providing guidance for the community to maintain harmony between religions in the contemporary era.